Поселення культури лійчастого посуду в Малих Грибовичах - Гавінський, А. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Settlement of funnel beaker culture in Mali Grybovychi is first of well-researched settlements in Western Ukraine. History of investigation of this monument and non-published collection of artifacts from excavations carried out by M. Smishko during 1933–1943 are presented at the article.